(untitled) (World Bulletin of Public Health, 2025)
This study presents a hygienic assessment of the nutritional status of workers employed in a tobacco production enterprise by determining their daily total energy expenditure. A total of 369 workers participated, including 324 men and 45 women, divided into control and experimental groups. The control group consisted of administrative, medical, and security staff, while the experimental group included employees directly involved in tobacco processing and cigarette production. The basal metabolic rate (BMR) was calculated using the Mifflin–St Jeor equations in accordance with Sanitary Rules and Hygiene Standards No. 007-2020. Daily energy expenditure was determined following the methodology of Sanitary Regulations No. 0250-08, taking into account seasonal variations and 24-hour activity chronometry. Results showed that the experimental group had significantly higher energy expenditure compared to the control group. Men demonstrated higher energy requirements than women across all seasons. The findings emphasize the need for gender- and season-specific dietary planning to maintain optimal health and to mitigate the harmful effects of tobacco exposure. This research provides a scientific basis for developing preventive and hygienically balanced nutrition programs for industrial workers.